2014
DOI: 10.1523/jneurosci.1854-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bed Nucleus of the Stria Terminalis Corticotrophin-Releasing Factor Receptors in Frustration Stress-Induced Binge-Like Palatable Food Consumption in Female Rats with a History of Food Restriction

Abstract: We developed recently a binge-eating model in which female rats with a history of intermittent food restriction show binge-like palatable food consumption after 15 min exposure to the sight of the palatable food. This "frustration stress" manipulation also activates the hypothalamic-pituitary-adrenal stress axis. Here, we determined the role of the stress neurohormone corticotropin-releasing factor (CRF) in stress-induced binge eating in our model. We also assessed the role of CRF receptors in the bed nucleus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 75 publications
7
51
0
Order By: Relevance
“…These compounds did not affect palatable food intake in control rats (Micioni Di Bonaventura et al, 2014). …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These compounds did not affect palatable food intake in control rats (Micioni Di Bonaventura et al, 2014). …”
Section: Discussionmentioning
confidence: 89%
“…We recently reported that systemic injections of the CRF1 receptor antagonist R121919 and bed nucleus of the stria terminalis (BNST) injections of the CRF receptor antagonist D-Phe-CRF (12–41) decreased frustration stress-induced binge eating in rats with a history of food restriction (Micioni Di Bonaventura et al, 2014). …”
mentioning
confidence: 99%
“…It is characterized by excessive consumption of highly palatable foods within short periods of time, accompanied by loss of control over eating (American Psychiatric Association, 2013). An increasing number of behavioral and neurobiological findings provide strong support for the consideration of binge eating disorder as an addiction-like disorder (Colantuoni et al, 2002; Corwin & Buda-Levin, 2004; Cottone, Sabino, Steardo, & Zorrilla, 2008; Micioni Di Bonaventura et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Core diagnostic criteria for binge-eating disorder include excessive consumption of food within brief periods of time, accompanied by loss of control, uncomfortable fullness, and intense feelings of disgust and embarrassment (APA, 2013). Growing evidence suggests that binge eating may result from neuroadaptative mechanisms in discrete areas of the brain that parallel drug and alcohol addiction (Avena et al, 2008;Corwin, 2006;Cottone et al, 2008b;Micioni Di Bonaventura et al, 2014;Parylak et al, 2012).…”
Section: Introductionmentioning
confidence: 99%